(untitled) (Advancements in Homeopathic Research, 2022)
One of the commonest infections in tropical countries is amoebiasis which is caused by Entamoeba histolytica. The spread of amoebiasis occurs by faecal-oral contamination and after an insidious onset, complaints of abdominal discomfort, flatulence of the bowels and recurring diarrhoea develop. The selection of the homeopathic medicine in a case of amoebiasis requires a thorough analysis and evaluation in details. Homeopathic medicines treat intestinal amoebiasis and also provide relief from symptoms of diarrhoea and abdominal pains. In the following case, a patient of geriatric age group came with clinical features of amoebiasis which was confirmed through laboratory test (routine examination of stool) showing cysts of Entamoeba histolytica. Pulsatilla 200 was given in fractional dilutional doses and the selection was not only based on miasmatic and repertorial analysis but also substantially supported by phytochemical analysis. This chemical analysis brought the simillimum from symptomatic level to molecular level.